Catalytic Activity of 0.4 % Rhodium Supported Microporous AlPO4-5 Catalyst for NO-CO-C3H6-O2 Reactions - Samed, Ahmed Jalal; Machida, Masato (Asian Journal of Chemistry, 2018)
Temperature-programmed reactions of mixtures of NO, CO, C3H6 and O2 were investigated over rhodium supported on microporous AlPO4-5 catalyst. Same reactions were studied after treating the catalyst in a stream of H2 to evaluate the catalytic performance after reduction treatment. Microporous AlPO4-5 was synthesized hydrothermally using triethylamine as structure directing agent and then been used as a support for rhodium metal. A lower amount of rhodium (0.4 wt %) supported on microporous AlPO4-5 catalyst exhibited satisfactory light-off at temperature (T50 % = 300 ºC) with a steep rise in conversion efficiency after aging the catalyst at 900 ºC for 25 h in a stream of 10 % H2O/air. Outstanding result was observed after reduction treatment of the catalyst, where light-off shifted to a lower temperature 200 ºC maintaining steep rise in conversion efficiency. Rhodium nanoparticles were well dispersed on the high surface area microporous AlPO4-5 material, which is believed to be the key factor for exhibiting excellent catalytic activity both in the oxidizing as well as reducing environment. This newly developed rhodium supported microporous AlPO4-5 catalyst with minimum rhodium loading having excellent catalytic performance after reduction treatment, has the potential to serve as a new generation there-way catalyst.